Holly (Ilex latifolia Thunb.) Polyphenols Extracts Alleviate Hepatic Damage by Regulating Ferroptosis Following Diquat Challenge in a Piglet Model - He, Pengwei; Hua, Hongwei; Tian, Wei; Zhu, Huiling; Liu, Yulan; Xu, Xiao (Frontiers in Nutrition, 2020)
Background: Holly (Ilex latifolia Thunb.) polyphenols extracts (HPE) contain high amounts of polyphenols including phenolic acids, triterpenoids, tannic acids and so on, which have strong antioxidant function. This study aimed to investigate the protective effect and mechanism of HPE against hepatic injury induced by diquat. Methods: Thirty-two weaned piglets were allotted in a 2 × 2 factorial experiment with dietary treatment (basal diet vs. HPE diet) and diquat challenge (saline vs. diquat). On d 21 of the trial, piglets were injected with diquat or saline. After 1 week later, blood samples were collected. Then all piglets were slaughtered and hepatic samples were collected. Results: Dietary HPE supplementation improves hepatic morphology, the activities of plasma aspartate aminotransferase, alanine aminotransferase and glutamyl transpeptidase, enhances hepatic anti-oxidative capacity, while regulates the expression of ferroptosis mediators (transferrin receptor protein 1, heat shock protein beta 1, solute carrier family 7 member 11, and glutathione peroxidase 4) in diquat-challenged piglets. Conclusion: These results indicate that dietary HPE supplementation enhances hepactic morphology and function, which is involved in modulating antioxidant capacity and ferroptosis.